Species delimitation and phylogenetic relationships of Silene villosa s.l. (Caryophyllaceae, sect. Silene s.l.) using nrDNA ITS and cpDNA rps16 - Farzaneh Jafari; Maryam Keshavarzi; Richard K. Rabeler (Plant Ecology and Evolution, 2022)
Background and aims – Species delimitation is a necessary investigation for widely distributed species. Examination of herbarium specimens and descriptions in local floras revealed that two forms of Silene villosa were recognized. Form B of S. villosa has been identified as a separate species named S. wendelboi. However, the latter species was not treated as a separate species in local floras. By using molecular tools, we investigated if these forms of S. villosa should be treated as two distinct species or be retained in S. villosa. Material and methods – We created two datasets containing 84 and 46 accessions of nrDNA ITS and cpDNA rps16 regions, respectively, which were extracted mainly from GenBank. Phylogenies were reconstructed using Maximum Likelihood and Bayesian analyses. Key results – We propose that S. villosa and S. wendelboi are two separate species, morphologically and phylogenetically. Silene wendelboi was first recognized in SW Iran but we show that the species is distributed in the Persian Gulf and the E Mediterranean region as well. In most cases, S. wendelboi is erroneously identified as S. villosa in these regions. The distribution of S. villosa is much wider, also occurring in SW Asia and North Africa, Egypt, and Algeria. Silene wendelboi differs from S. villosa in calyx texture, calyx length, the ratio of calyx length to pedicel, the shape of the apex of the coronal scale, seed morphology, and molecular data, i.e. ITS and rps16 sequences. Based on those two markers, S. villosa is closely related to S. ayachica, while S. wendelboi shows affinity to S. arabica.